2010
DOI: 10.2478/v10036-010-0001-x
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Aspects of Work in Hypoxic Conditions - The New Recommendation of the Medical Commission of the Union Internationale des Associations d'Alpinisme (UIAA MedCom)

Abstract: More and more persons are exposed to hypoxia while working at altitude, e.g. when working for cable cars or ski areas in the Alps, for business in South America or Asia, as airline crews, or in rooms with reduced oxygen pressure for hypoxia training or fire protection. Unfortunately, the different countries have a multitude of regulations for occupational health and safety concerning hypoxia -most of them with major deficiencies and a significant lack of knowledge about hypoxia and possible specific risks. So … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 34 publications
0
14
0
3
Order By: Relevance
“…increased pulse rate, hyperventilation, increase of hemoglobin mass, higher capillary density, increased hypoxic ventilatory response, reduced hypoxic pulmonary pressure response etc. [survey in Ward et al (2000), Kupper et al (2010)]. Some mechanisms take effect within seconds (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…increased pulse rate, hyperventilation, increase of hemoglobin mass, higher capillary density, increased hypoxic ventilatory response, reduced hypoxic pulmonary pressure response etc. [survey in Ward et al (2000), Kupper et al (2010)]. Some mechanisms take effect within seconds (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Both effects lasted for at least 1 h after the noise exposure was ended and a complete recovery was reached after a much longer period (3 h). Attitas et al showed in their animal model that a TTS occurred after an isobaric exposure to 6% oxygen (Attias et al 1990), which corresponds to an altitude of about 10,500 m (Ernsting and King 1994;Kupper et al 2010). The finding that acclimatized animals showed significantly lesser hearing impairment supports the thesis of the combined effect of noise and hypoxia (Berndt et al 1978).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Typically alpine rescue takes place at altiudes between 2500 and 4600 m (Küpper, 2006). At these altitudes oxygen pressure is reduced by a third (Ruff and Strughold, 1944;Muller, 1967;Ernsting and King, 1988;Küpper et al, 2010). Hearing is an active, energy consuming process and this energy is provided inside the cochlea over a relatively long diffusion distance.…”
Section: Discussionmentioning
confidence: 99%
“…More and more people try to climb it within 3-4 days and only a minority reaches the summit healthy [1]. Businessmen are another group with limited time or unforeseen trips to high altitude [2]. Principally, correct acclimatization was, is, and will ever be the "gold standard" for any altitude sojourn [3].…”
Section: Introductionmentioning
confidence: 99%